Gernu : an approach to cloud management based on user requirements , dynamic creation of services and definition of quality attributes - Helder Pereira Borges (2013)
Cloud Computing has been established in recent years as an important area of research. This paradigm has been consolidated, since tasks such as obtaining, handling, sharing and exploitation of large amounts of data are becoming increasingly common, requiring many computing resources. Considering this context, cloud computing can help providing these resources indefinitely, including memory, processing, storage and others, all of them for immediate use. The provision of cloud services involves several complex tasks. To increase the user satisfaction, these tasks need to consider issues relevant to them, in addition to the providers' policies. In order to define a flexible process for specification and procurement of services in clouds from the hardware and software requirements of users, this work proposes an approach that uses a virtual environment model containing all the relevant information to provide a personalized service. Another key challenge for cloud computing is related to the services quality control. This aspect may be directly affected by resource utilization. Thus, the use of automated mechanisms to provide services, monitoring resources, as well the quality of services also helps to increase the level of customer satisfaction, creating an environment less susceptible to errors for the administrators. Besides the aspects of hardware and software, the virtual environment model will contain the quality of service attributes, having been set an automated negotiation process that occurs concomitantly with the procurement service process. Thus, this approach will be able to automatically deliver infrastructure, platform and software as a service from the user's specific requirements.